2019
DOI: 10.2147/cmar.s175886
|View full text |Cite
|
Sign up to set email alerts
|

<p>Defining unmet clinical need across the pathway of brain tumor care: a patient and carer perspective</p>

Abstract: ObjectiveThe aim of this study was to determine the experience of patients with brain tumors and their carers across distinct parts of their treatment pathway and identify their views on potential service gaps in need of addressing.MethodsA structured survey was administered at patient workshops across the UK and online through a charity newsletter. Answers to closed questions were analyzed using descriptive statistics, and open questions were examined using techniques of inductive content analysis.ResultsA to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…Twelve studies used qualitative methodologies, 4 , 13 , 20 – 22 , 25 27 , 29 – 32 two adopted a mixed-methods approach, 23 , 28 and the remaining two purely quantitative methodology. 11 , 24 Most studies conducted semistructured interviews with individuals (n = 8), 4 , 13 , 20 – 22 , 25 , 27 , 32 focus groups (n = 1), 29 or both (n = 3).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twelve studies used qualitative methodologies, 4 , 13 , 20 – 22 , 25 27 , 29 – 32 two adopted a mixed-methods approach, 23 , 28 and the remaining two purely quantitative methodology. 11 , 24 Most studies conducted semistructured interviews with individuals (n = 8), 4 , 13 , 20 – 22 , 25 , 27 , 32 focus groups (n = 1), 29 or both (n = 3).…”
Section: Resultsmentioning
confidence: 99%
“…Of all sixteen studies, eleven sampled patients, 4 , 11 , 13 , 20 , 24 26 , 28 , 30 32 eight sampled carers, 21 , 23 , 25 27 , 29 – 31 and five sampled HCPs. 4 , 23 , 25 , 26 , 31 All studies that sampled carers were identified as members of the patient’s family and one included an unrelated friend.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations